Analisis Implementasi SIMRS di Indonesia Berbasis Kerangka TOE: Studi Kasus di Rumah Sakit Umum Kaliwates - LUKMAN HAKIM (Politeknik Kementerian Kesehatan Banjarmasin, 2026)
Digital transformation compels hospitals to adopt Hospital Management Information Systems (HMIS) to enhance service quality. Kaliwates General Hospital has implemented HMIS but faces challenges related to infrastructure, organizational readiness, and sub-optimal administrative time efficiency. The objective of this study is to analyze the factors influencing HMIS Adoption at Kaliwates General Hospital using the Technology-Organization-Environment (TOE) framework. This research is an observational analytic study with a cross-sectional method, conducted at Kaliwates General Hospital involving 121 respondents (70 Medical Services respondents and 51 Clinical & Non-Clinical Support respondents). The analysis employed the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach. The results indicate that the model demonstrates strong explanatory power (RÂ² of HMIS Adoption > 65%). All three TOE factors (Technology, Organization, and Environment) significantly influence HMIS Adoption. The Technology factor was the most dominant (Î² = 0.511), followed by Organization (Î² = 0.234), and Environment (Î² = 0.171). In conclusion, although HMIS adoption is already high, the Organizational factor still requires improvement. Long-term implementation success depends on optimizing organizational support through consistent managerial policies, continuous training, and enhanced human resource capacity. These findings can guide policymakers in strengthening digital readiness and organizational management in hospital settings.